2008
DOI: 10.1111/j.1744-7909.2008.00733.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities Occurring during Female Gametophyte Development Result in the Diversity of Abnormal Embryo Sacs and Leads to Abnormal Fertilization in indica/japonica Hybrids in Rice

Abstract: Embryo sac abortion is one of the major reasons for sterility in indica/japonica hybrids in rice. To clarify the causal mechanism of embryo sac abortion, we studied the female gametophyte development in two indica/japonica hybrids via an eosin B staining procedure for embryo sac scanning using confocal laser scanning microscope. Different types of abnormalities occurred during megasporogenesis and megagametogenesis were demonstrated. The earliest abnormality was observed in the megasporocyte. A lot of the chal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 21 publications
2
21
0
3
Order By: Relevance
“…Abnormal female gametophyte of hybrid F 1 appears at the eight-nucleate embryo sac developing stage, when polar nuclei start their migration to the upward side of the egg apparatus and the embryo sac begins to enlarge (Figure 2). In addition, the abnormal embryo sac caused by S7 led to the semisterility of spikelets directly (Table 2), which was consistent with a previous report that most of the smaller embryo sacs and abnormal polar nuclei positioning embryo sacs could not succeed in fertilization, even with a normal female germ unit (Zeng et al 2009). It was reported that orientation of polar nuclei always occurred not only during development of female gametophyte but also after fertilization, when one sperm cell nucleus moved toward the central cell (Ding et al 2009).…”
Section: S7 Encodes a Tpr-containing Proteinsupporting
confidence: 80%
“…Abnormal female gametophyte of hybrid F 1 appears at the eight-nucleate embryo sac developing stage, when polar nuclei start their migration to the upward side of the egg apparatus and the embryo sac begins to enlarge (Figure 2). In addition, the abnormal embryo sac caused by S7 led to the semisterility of spikelets directly (Table 2), which was consistent with a previous report that most of the smaller embryo sacs and abnormal polar nuclei positioning embryo sacs could not succeed in fertilization, even with a normal female germ unit (Zeng et al 2009). It was reported that orientation of polar nuclei always occurred not only during development of female gametophyte but also after fertilization, when one sperm cell nucleus moved toward the central cell (Ding et al 2009).…”
Section: S7 Encodes a Tpr-containing Proteinsupporting
confidence: 80%
“…Moreover, some mutant embryo sacs defective in cellular patterning/cell specification contained nuclei of a different size and, occasionally, partly degenerated micronuclei, similar to findings in dsul mutant ovaries. The cytological analysis of partly sterile indica/japonica hybrids in rice indicated that sterility was mainly caused by FG development defects (Zeng et al, 2009). The phenotypes described partly overlap with those described for dsul mutant ovaries: the eight-nucleus stage was shown to be most severely affected by asynchronous nuclear migration and abnormal positioning of nuclei, as well as egg apparatus or complete FG degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The degeneration of the entire embryo sac preceded by atypical megasporocyte was described in the indica/japonica hybrid. Although no irregularities were observed during the division of the megasporocyte, most of them occurred after meiosis, when some abnormal megaspores failed to form typical mononucleate embryo sacs (Liu et al, 2004;Zeng et al, 2009). On the other hand, investigation of female meiosis in A. roylei (Sharma and Gohil, 2011) resulted in identification of additional chromosomes and multivalents in embryo sac mother cells that, as the authors suggest, may adversely affect the reproductive capacity and lead to production of genetically imbalanced gametes.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormalities that occur during megasporogenesis and megagametogenesis in the plants of F 1 generation are the most likely result of incongruity and defects which occur in developmental processes (Winiarczyk, 1999;Mangum and Peffley, 2005). In embryological studies of indica/japonica hybrids in rice irregularities both in megasporocytes and embryo sacs were observed (Zeng et al, 2009). The abnormalities that occurred from the early stage of the eight-nucleate embryo sac development to the mature embryo sac stage included smaller in size and wrinkled antipodals, asynchronous nuclear migra- tion, abnormal positioning of nucleus and degeneration of egg apparatus.…”
Section: Discussionmentioning
confidence: 99%